An International Comparison of the Instigation and Design of Health Registers in the Epidemiological Response to Major Environmental Health Incidents. Issue 1 (January 2017) - Behbod, Behrooz; Leonardi, Giovanni; Motreff, Yvon; Beck, Charles R.; Yzermans, Joris; Lebret, Erik; Muravov, Oleg I.; Bayleyegn, Tesfaye; Wolkin, Amy Funk; Lauriola, Paolo; Close, Rebecca; Crabbe, Helen; et al.
Abstract : Context: Epidemiological preparedness is vital in providing relevant, transparent, and timely intelligence for the management, mitigation, and prevention of public health impacts following major environmental health incidents. A register is a set of records containing systematically collected, standardized data about individual people. Planning for a register of people affected by or exposed to an incident is one of the evolving tools in the public health preparedness and response arsenal. Objective: We compared and contrasted the instigation and design of health registers in the epidemiological response to major environmental health incidents in England, France, Italy, the Netherlands, and the United States. Design: Consultation with experts from the 5 nations, supplemented with a review of gray and peer-reviewed scientific literature to identify examples where registers have been used. Setting: Populations affected by or at risk from major environmental health incidents in England, France, Italy, the Netherlands, and the United States. Methods: Nations were compared with respect to the (1) types of major incidents in their remit for considering a register; (2) arrangements for triggering a register; (3) approaches to design of register; (4) arrangements for register implementation; (5) uses of registers; and (6) examples of follow-up studies. Results: Health registers have played a key role in the effective public health response to major environmental incidents, including sudden chemical, biological, radiological, or nuclear, as well as natural, more prolonged incidents. Value has been demonstrated in the early and rapid deployment of health registers, enabling the capture of a representative population. Conclusion: The decision to establish a health register must ideally be confirmed immediately or soon after the incident using a set of agreed criteria. The establishment of protocols for the instigation, design, and implementation of health registers is recommended as part of preparedness activities. Key stakeholders must be aware of the importance of, and protocols for, establishing a register. Agencies will find value in preparing and implementing registers as part of an effective public health response to major environmental incidents, including sudden chemical, biological, radiological, or nuclear incidents, as well as natural, more prolonged incidents. Abstract : Supplemental Digital Content is Available in the Text.